Epidemiology of female youth ice hockey injuries presenting to United States emergency departments from 2002 to 2019. Issue 5 (3rd September 2022) - Morrissey, Patrick J.; Zhou, Jack J.; Shah, Neil V.; Torre, Barrett B.; Dekis, Joanne C.; Newman, Jared M.; Connors, Katherine M.; Urban, William P.
ABSTRACT: Background: This study documented injury types, rates and mechanisms for female youth ice hockey players reporting to US emergency departments to inform safety measures and sideline medical preparedness. Methods: The National Electronic Injury Surveillance System (NEISS) database was queried for ice hockey injuries (product code 1279) from 1 January 2002 to 31 December 2019. Incidence rate ratios (IRR) were calculated using OpenEpi and compared between age divisions. Spearman's rank correlation was utilized to evaluate the correlation between age and injury incidence. USA Hockey membership statistics were used to establish the population at risk and calculate incidence rates (IR). Results: An estimated 20, 384 ice hockey injuries presented to participating United States emergency departments. The number of female youth ice hockey players increased significantly from 36, 258 in 2002 to 65, 072 in 2019 (p < 0.01). The most commonly injured body parts were the head ( n = 5, 519, IR = 62.1 [95%CI 54.3–70.0 per 10, 000 athletes), trunk ( n = 2, 364, IR = 26.6 [95%CI 21.2–32.0] per 10, 000 athletes), and wrist ( n = 1, 824, IR = 20.5 [95%CI 15.7–25.4] per 10, 000 athletes). The most commonly reported mechanisms of injury were player-to-player collision ( n = 4, 746, IR = 53.4 [95%CI 46.4–60.5] per 10, 000 athletes) and falls ( n = 4, 585, IR = 51.6 [95%CI 44.1–59.1] per 10, 000 athletes). The most common diagnoses were traumatic brain injury (n = 5, 333, IR = 60.0 [95%CI 52.3–67.8] per 10, 000 athletes), contusion (n = 4, 204, IR = 47.3 [95%CI 40.3–54.4] per 10, 000 athletes) and strain/sprain (n = 3, 601, IR = 40.5 [95%CI 34.1–47.0] per 10, 000 athletes). A positive correlation was found between age and injury incidence, as well as increasing age and injuries from player-to-player collision and TBI's. Conclusions: Though body checking is illegal at all levels of women's ice hockey, player-to-player collision prevailed as the leading mechanism on injury. Hopefully this study informs players, parents, coaches, trainers and clinicians about the impact of player-to-player collisions on overall injury burden in the older age divisions of youth female hockey.